1999
DOI: 10.1037/0735-7044.113.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between 192-IgG saporin and intraseptal cholinergic and GABAergic drugs: Role of cholinergic medial septal neurons in spatial working memory.

Abstract: Rats were administered 192-IgG saporin (SAP) or vehicle into the medial septum-vertical limb of the diagonal band (MS-vDB). Starting 1 week later, the effects of intraseptal scopolamine, oxotremorine, and muscimol were tested in a T-maze alternation task. Choice accuracy in the absence of infusions did not differ between control and SAP-treated rats. Intraseptal scopolamine or muscimol impaired the choice accuracy of SAP-treated but not control rats. Oxotremorine impaired accuracy similarly in control and SAP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
2

Year Published

2001
2001
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 43 publications
3
58
2
Order By: Relevance
“…It means only that elevating ACh is sufficient to overcome the deficit, perhaps, for example, by increasing compensatory responses (Björklund and Dunnett 1995). Indeed, the hypothesis that septal GABA receptor activation impairs memory exclusively via an effect on hippocampal ACh is not supported by the finding that septal infusions of muscimol still impair memory when the septohippocampal cholinergic projection is lesioned (Pang and Nocera 1999). On the other hand, a wealth of evidence indicates that septal GABA receptor activation does likely impair memory through a process that involves, at least in part, inhibition of hippocampal ACh.…”
Section: Upregulation Of Hippocampal Ach Reverses Septal Memory Deficitsmentioning
confidence: 83%
See 3 more Smart Citations
“…It means only that elevating ACh is sufficient to overcome the deficit, perhaps, for example, by increasing compensatory responses (Björklund and Dunnett 1995). Indeed, the hypothesis that septal GABA receptor activation impairs memory exclusively via an effect on hippocampal ACh is not supported by the finding that septal infusions of muscimol still impair memory when the septohippocampal cholinergic projection is lesioned (Pang and Nocera 1999). On the other hand, a wealth of evidence indicates that septal GABA receptor activation does likely impair memory through a process that involves, at least in part, inhibition of hippocampal ACh.…”
Section: Upregulation Of Hippocampal Ach Reverses Septal Memory Deficitsmentioning
confidence: 83%
“…Impairments have also been reported in acquisition and performance of a delayed matching-to-place task in the T-maze (Gibbs 2002;Johnson et al 2002) following lesions limited to MS/VDB cholinergic neurons. However, nonmatching-to-place in the Tmaze is not impaired following MS/VDB cholinergic lesions (Pang and Nocera 1999;Kirby and Rawlins 2003). Because the memory requirement in the two tasks is equivalent, the matching deficits may reflect an inability to apply a behavioral rule that is contrary to the rat's spontaneous nonmatching behavior, rather than an impairment in spatial memory per se.…”
Section: Lesions Of the Medial Septum Or Its Projectionsmentioning
confidence: 92%
See 2 more Smart Citations
“…However, a recent study in which cholinergic neuron integrity at the lesion site was verified found impairment in spatial working memory after 192 IgGsaporin lesions of the MS/VDB (Lehmann et al 2003), suggesting that these lesions can be sufficient to impair spatial memory under some circumstances. Studies examining spatial working memory using rewarded T-maze alternation have not found effects of cholinergic MS/VDB lesions (Pang and Nocera 1999;Kirby and Rawlins 2003). These differences across studies also do not appear to be related to whether the lesion is given before training on the maze task, or afterward.…”
mentioning
confidence: 86%